1999
DOI: 10.1016/s0042-6989(98)00300-9
|View full text |Cite
|
Sign up to set email alerts
|

Axis-of-motion affects direction discrimination, not speed discrimination

Abstract: The motion of an object can be described by a single velocity vector, or equivalently, by direction and speed separately. Similarly, our ability to see subtle differences in the motion of two objects could be constrained by either a velocity-based sensory response, or separate sensory responses to direction and speed. To distinguish between these possibilities we investigated whether direction discrimination and speed discrimination were differentially affected by changes in the axis-of-motion. Psychophysical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 13 publications
5
47
3
Order By: Relevance
“…Our data indicating that orientations are unequally represented in MT suggest an explanation for the behavioral finding that humans have a greater sensitivity to motion in cardinal directions than in oblique directions (7,(19)(20)(21)(22). Because neurons in MT are highly selective for both direction of motion and stimulus orientation, orientation specific differences in motion perception could be mediated, at least in part, by neurons in MT.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our data indicating that orientations are unequally represented in MT suggest an explanation for the behavioral finding that humans have a greater sensitivity to motion in cardinal directions than in oblique directions (7,(19)(20)(21)(22). Because neurons in MT are highly selective for both direction of motion and stimulus orientation, orientation specific differences in motion perception could be mediated, at least in part, by neurons in MT.…”
Section: Discussionmentioning
confidence: 61%
“…Neurons of similar orientation or direction-of-motion selectivity are clustered into functional columns in MT (15-18). In addition, an oblique effect has been observed in humans for the perception of objects moving in cardinal vs. oblique directions (7,(19)(20)(21)(22). Because of a preponderance of direction-selective neurons, MT is thought to be important to the processing of visual motion (14).…”
mentioning
confidence: 99%
“…A wide variety of visual tasks show better performance with horizontally or vertically oriented contours than with oblique ones (Appelle, 1972). There is consensus that the locus for this oblique effect is cortical because it manifests itself in such thresholds as line-orientation and alignment discrimination and the orientation of streaming random dots (Matthews and Qian, 1999;Westheimer, 2003b) but not in those depending predominantly on retinal processing, such as detection of the presence or discrimination of brightness of single lines, and to some extent also of resolution (Westheimer and Beard, 1998). Most of these experiments were performed with central vision, but when specifically looked for, an oblique effect can also be found in the periphery of the visual field (Davis and Zanker, 1998;Vandenbusche et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The reasoning behind the latter manipulation was that for the processing of visual motion it has been suggested that separate mechanisms may be employed for the processing of direction and speed (e.g. Matthews & Qian, 1999;Matthews, Luber, Qian, & Lisanby, 2001), and we wanted to explore if a similar separation might exist in the auditory domain. For example, if sound motion direction was processed separately from sound motion speed, one might observe a deficit in the perception of sound motion direction whilst perception of sound motion speed might be normal, or vice versa.…”
mentioning
confidence: 99%